PENGARUH PENAMBAHAN CAMPURAN BUAH APEL, PIR, DAN ALPUKAT TERHADAP KUALITAS YOGURT BERDASARKAN PARAMETER RASA, KEKENTALAN, DAN KEASAMAN PRODUK - Muliana; Mutmainna, Andi; Anisa Putri, Apni; Naila Maharani, Andi; Lestari, Putri; Kastan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Yogurt is a fermented milk product that contains probiotic bacteria and provides various health benefits. The addition of fruits to yogurt is commonly used to improve its nutritional value and sensory characteristics. This study aimed to determine the effect of adding apple, pear, and avocado on yogurt quality. The research employed an experimental method by mixing apple, pear, and avocado into fermented yogurt. The observed parameters included color, aroma, taste, and texture. The results showed that the addition of the fruit mixture affected the sensory quality of yogurt. The yogurt produced had a more attractive appearance, a fresher aroma, a sweeter taste, and a softer texture than plain yogurt. The nutritional content of the yogurt also increased due to the vitamins, minerals, and fiber contained in the fruits. Therefore, the addition of apple, pear, and avocado can improve yogurt quality and increase consumer acceptance.